Manual of obstetrics (Lippincott Williams & Wilkins, 2000)
This edition's chapters have a new consistent outline structure, more tables, and more figures. Coverage includes a new chapter on obstetric anesthesia and new information on drugs for cardiovascular, neurologic, and endocrine conditions, including oral agents for gestational diabetes. The chapter on genetic counseling has been completely rewritten. This edition also addresses controversies regarding surgical births and vaginal birth after cesarean (VBAC).